Biomimetic and protective effects of bioactive toothpastes on eroded enamel surfaces - Oliveira, Andressa Feitosa Bezerra de; Nunes, Vitória Régia Rolim; Cunha, Juliellen Luiz da; Forte, Anderson Gomes; Andrade, Arthur Felipe de Brito; Fernandes, Nayanna Lana Soares; Pereira, Ana Maria Barros Chaves; D'Alpino, Paulo Henrique Perlatti [UNESP]; Sampaio, Fábio Correia (FapUNIFESP (SciELO), 2024)
This study aimed to evaluate the effectiveness of bioactive toothpastes in remineralizing eroded enamel surfaces in vitro. Bovine enamel blocks (n = 48) were obtained and classified into untreated, demineralized, and treated areas. Specimens were randomly classified into six groups (n = 8 each): fluoride-free toothpaste (NCT), Colgate Total 12 (PCT), Sensodyne Repair and Protect (SRP), Sensodyne Pronamel (SPE), Regenerador + Sensitive (RGS), and RGS/calcium booster (RCB). The specimens were subjected to erosive pH cycling for 5 days for 4 times/day (90 s) and treated with toothpaste slurries (1:3) for 1 min. The Vickers hardness (50 g/10 s) and percentage surface hardness recovery (%SMHR) were calculated. Furthermore, the topography and roughness (Ra) of the enamel surface were evaluated using a 3D non-contact optical profilometer, along with the tooth surface loss (TSL). Data were statistically analyzed using analysis of variance or Tukey's test (significance: 5%). The %SMHR of the SRP and NCT groups were significantly lower than those of the other groups (p < 0.05). Ra was higher when the eroded area was treated with SRP and SPE (p < 0.05). Treatment with RGS, PCT, and SPE favored the recovery of the enamel surface compared with the NCT group (p < 0.05). The best TSL results were obtained with treatment with RGS, followed by PCT and SPE (p < 0.05). The RCB group showed statistically equivalent results for surface hardness recovery and TSL (p > 0.05). Conclusively, PCT and RGS toothpastes were more effective in remineralizing the enamel surface.
Keywords: Dental Enamel; Hardness; Surface Properties; Tooth Remineralization; Toothpastes